PENGARUH PUPUK KANDANG SAPI DAN JARAK TANAM TERHADAP PERTUMBUHAN SERTA HASIL JAGUNG SEMI (BABY CORN) DAN KACANG HIJAU (Vignaradiata L.) PADA POLA TUMPANGSARI - Prima Janti Arisana; Armaini Armaini; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to observe the effect of cow manure dose and spacing in their interaction and obtain the best dose of cow manure and suitable spacing to baby corn and mungbean growth and yield on intercropping system. This research has been conducted at the experimental farm, Agricultural Faculty of Riau University on Januari to April 2016.The research was carried out experimentally using a completely randomized design with 2 factors. The first factor was dose of cow manure, consisted of 4 treatments 10 tons/ha, 15 tons/ha, 20 tons/ha and 25 tons/ha. The second factor was spacing, consisted of 2 treatments 75 x 20 cm and 75 x 40 cm. Data obtained were statistically analyzed using analysis of variance and continued with Duncan’s New Multiple Range Test (DNMRT) at 5% level. The results showed that the interaction of cow manure and spacing no real effect on all treatments. Combination of 20 ton/ha cow manure and spacing at 75 cm x 40 cm were the best treatment to baby corn and mungbean growth and yield.Keywords : Cow manure, Spacing, Baby corn, Mungbean